Características antropométricas dos pés de indivíduos idosos - Castro, Alessandra Paiva de (Universidade Federal de São Carlos, 2007)
The changes due to senescence induce anatomical modifications in the foot which leading the older persons to have difficulty to find comfortable and safe shoes. The aims of this study were to identify the peculiar anthropometric characteristics of the elderly foot in São Carlos City, becoming possible the development of appropriate shoes for elderly population; and to verify relations between anthropometric variables and wearing incorrectly sized shoes, gender, age, foot pain, foot posture and diseases. The sample was calculated based on elderly population of São Carlos City and following its gender and age group proportions. Took part of this study 399 individuals between 60 and 90 years of age, of both genders (227 women and 172 men). The participants answered a questionnaire concerning social aspects, orthopedic assessment and questions related to the use of shoes. The anthropometric evaluation of the feet comprised variables of lengths, circumferences, widths, heights, angles, Arch Index and Foot Posture Index. The data analysis was performed using the T-student test, Analysis of Variance, Tukey test, probability analysis, chi-square test and Pearson s Correlation. The characterization of the foot of the elderly in São Carlos City was done using descriptive analysis (means, standard deviation, minimal and maximal values and standard error) and the means and standard deviation were distributed by intervals of foot lengths according to the shoe size.The participants wearing the incorrect shoe size presented larger values for widths, heights, perimeters and first metatarsophalangeal joint angle than those wearing the correct size. Women had feet proportionally wider, flatter and more abducted, while men had feet proportionally higher than women. Lower limb pain and pain associated with wearing shoes were correlated with the female gender and wearing the incorrect shoe size was correlated with the male gender. There was found a negative middle correlation between the Foot Posture Index and the instep and medial malleolus heights. The proportion of flat and cavus feet was high. Elderly with flat feet had more pronated feet, greater bulging in the region of talonavicular joint and smaller height of first metatarsal head, foot curvature, instep and medial malleolus. The obtained data can possibilities design shoes based on the specific anthropometric measurements of the elderly population.
Keywords: Gerontologia; Envelhecimento; Antropometria; Pés; Calçados; Dor; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL